African-American Fathers’ Perspectives on Their Children’s Health Education: A Qualitative, Exploratory Study - Odum, Mary; Smith, Matthew Lee; McKyer, E. Lisako J. (Frontiers in Public Health, 2014)
Purpose: To investigate African American fathers’ perceptions regarding the applicability and need for their involvement as a health connection for their children and describe how participating fathers’ behavior was affected by their attitudes, knowledge, and perceptions of their influence on their children’s health. Methods: This exploratory study gathered data via semi-structured focus groups (n=3) and thematically analyzed it utilizing a grounded theory approach. Participants included African American fathers (n=20) with a mean age of 37 years (SD 11.79), with at least one child between 6-18 years old. Results: Four major themes were revealed: (1) appropriate health education for participants’ children (should first and foremost be delivered by parents); (2) participants’ paternal health-related guidance approach (reactive, rather than proactive); (3) participants’ perceived influences on health-related communication with their children (gender roles, efficacy constraints); and (4) paternal definitions of health (most often associated with diet). Conclusion: Understanding African American fathers’ perceived and desired role in their children’s health edification can inform initiatives that actively engage these men, and nurture their level of involvement, to promote positive health behaviors among their children; this is necessary to realize their potential to actively improve the health of their children, families, and communities.